The significance of trade policy in promoting the international competitiveness of South African industry - Hofmeyr, Lynne Mary (Rhodes University, Faculty of Humanities, Department of Political Studies, 1996)
This study proposes to examme the significance of trade policy in promoting the international competitiveness of South African industry during the period from the early 1970s up until the present day. By providing a background of South Africa's past trade policies, it is argued that the origins of South Africa's low levels of competitiveness essentially lie in the apartheid years where trade policies were not linked to the attainment of international competitiveness and improved productivity. The study then reviews the development of South Africa's trade policies in the 1990s. In so doing, it reveals weaknesses in the areas of implementation which are critiqued in greater detail by using the clothing and textile industries as a case study, and other selected examples. The study finally concludes that trade policy is crucial to global competitiveness and that it is the responsibility of all parties concerned to ensure that trade policies enhance and not inhibit competitiveness.
Keywords: South Africa -- Commerce|South Africa -- Commercial policy|International trade